Big data and intelligent decision methods in economy, innovation and sustainable development - Li, Deng-Feng; Liu, Pei-De (Technological and Economic Development of Economy, 2020)
Big data and intelligent decision methods in economy, innovation and sustainable development. Technological and Economic Development of Economy, 26(5), pp. 970-973.